PAN-AFRICANISM AND EDUCATION : AN EXPLORATORY STUDY OF AFRICAN CENTERED SCHOOLS IN CAMEROON AND SOUTH AFRICA - Caesar, Tiffany (Commonwealth Youth and Development, 2017)
â€œUmuntu Ngumuntu Ngabantuâ€ translates into a person is a person because of people. There is an idea of unity in this frequently used Zulu proverb that is posted boldly next to the Afrocentric logo on the African Union International School (AUIS) website in Midrand South, Africa. All these words are factors within Pan-Africanism, and AUIS is more than an international school in South Africa, but it is one of two schools created by the African Centered Educational Foundation (ACE). The other school is called the African American Academy in Douala, Cameroon. Under the auspice of ACE, both schools share a very special mission implied within its vision that includes an education for the African Renaissance. Through a content analysis, this paper will illustrate how the African Centered Education Foundation represents Pan-Africanism through the institutionalization of African Centered Education illustrated by their technological media (school websites, facebook, online articles), educational tools (brochures, teacher evaluations, lesson plans, teacherâ€™s introduction package), and their African diaspora volunteer teacher program.